Effectiveness of Ketapang Leaf (Terminalia catappa), Banana Leaf (Musa sp.), and Teak Leaf (Tectona grandis) Extracts on Enhancing the Color of Channa Maru Fish (Channa marulioides) - Putri, Rizka Rahmana; Qurtuby, Ahmad (Barakuda 45: Jurnal Ilmu Perikanan dan Kelautan, 2025)
This study aimed to evaluate the effectiveness of Ketapang (Terminalia catappa), Banana (Musa sp.), and Teak (Tectona grandis) leaf extracts on enhancing the coloration of Channa maru (Channa marulioides). Body coloration in ornamental fish is an important aesthetic trait that significantly influences market value and consumer preference in the ornamental aquaculture industry. The experiment was conducted using a completely randomized design (CRD) consisting of four treatments (control, Ketapang extract, Banana leaf extract, and Teak leaf extract) with three replications. Parameters observed included color intensity using the Toca Colour Finder (TCF), carotenoid content in fish tissues, survival rate, absolute growth in length and weight, and water quality. The results showed that Ketapang leaf extract significantly improved fish coloration, yielding the highest TCF scores and carotenoid content (0.32 µg/g), followed by Teak leaf extract (0.22 µg/g), Banana leaf extract (0.07 µg/g), and the control (0.06 µg/g). Leaf extracts had no significant effect on survival rate or absolute growth in length and weight. Water quality remained within the optimal range throughout the experiment and did not act as a limiting factor. In conclusion, Ketapang leaf extract is recommended as the most effective natural additive to enhance the coloration and carotenoid content of Channa maru, followed by Teak leaf extract, while Banana leaf extract showed less effectiveness.